2006
DOI: 10.1088/0960-1317/16/7/012
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of dry stiction in micro electro-mechanical systems (MEMS)

Abstract: Stiction, a term commonly used in micro electro-mechanical systems (MEMS) to refer to adhesion, is a major failure mode in MEMS. Undesirable stiction, which results from contact between surfaces, can severely compromise the reliability of MEMS. In this paper, a model is developed to predict the dry stiction between uncharged micro parts in MEMS. In dry stiction the interacting surfaces are assumed to be either hydrophobic or placed in a dry environment. In this condition the van der Waals (vdW) and asperity de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Another function should be defined to represent the spatial horizontal correlation of ordinates. A widely used function, under the assumptions of stationary and ergodicity of the surface, is the exponential autocorrelation function (ACF), [1]. The ACF allows the determination of a characteristic length related to the spatial occurrence of given surface heights and thus, of the number of interacting asperities.…”
Section: A Greenwood-williamson Model and Adhesive Contact Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…Another function should be defined to represent the spatial horizontal correlation of ordinates. A widely used function, under the assumptions of stationary and ergodicity of the surface, is the exponential autocorrelation function (ACF), [1]. The ACF allows the determination of a characteristic length related to the spatial occurrence of given surface heights and thus, of the number of interacting asperities.…”
Section: A Greenwood-williamson Model and Adhesive Contact Theorymentioning
confidence: 99%
“…In industry [1], several applications, such as accelerometers, digital mirror devices, pressure sensors, gyroscopes or resonators have been realized using MEMS technologies and many new applications are under development. In spite of those advantages, the inherent characters of MEMS, such as, the large surface-area to volume ratio, the relatively smoothness of the surfaces, the small interfacial gaps and the small restoring forces make them particularly vulnerable to the surface forces that could lead to permanent adhesion of MEMS moving parts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a dry and low-pressure environment, capillary forces will be relatively small, and the dominative factor of in-use stiction is the van der Waals forces between the molecules. 8,9 The use of atomic force microscopes ͑AFMs͒ and of surface force apparatuses, which allow for the accurate measurement of surface forces when the dimensions of contacting bodies are small, has shown that surface roughness plays an important role in the magnitude of the pull-out force between two bodies. The characterization of surface roughness is challenging because asperity distribution on the surface is not uniform.…”
Section: Introductionmentioning
confidence: 99%